0153 Risk of bladder cancer in a cohort of chemical workers. (21st August 2017) - Taeger, Dirk; Pesch, Beate; Kay-Gerald, Bierfreund; Oberlinner, Christoph; Leng, Gabriele; Arnulf, Stenzl; Kluckert, Matthias; Brüning, Thomas
Abstract : Objective: Bladder cancer is the fourth most frequent cancer among men in Germany. Aromatic amines can cause bladder cancer and therefore cancerogenic aromatic amines have been banned a long time ago from workplace, but a long latency can still increase the risk of former exposed workers. In this study, we will assess the risk of bladder cancer in a cohort of chemical workers with earlier use of aromatic amines compared to the general population. Methods: In the prospective cohort study UroScreen, 1800 former chemical workers exposed to aromatic amines were offered to participate in an early detection of bladder cancer by means of tumour markers. In 2003–10, 1609 people were examined at least once. The exposure to aromatic amines was determined by means of questionnaires. The observed bladder cancer incidence was compared with the expected incidence in the general population. Bladder cancer risk was estimated as standardised incidence ratio. Results: Nine incidence urinary bladder carcinoma occurred during the study. Eight cases were ex-smokers and one case was non-smoker. All cases were exposed for at least 10 years, including six cases longer than 20 years. Compared to the general population, the risk of bladder cancer was 2.94 (95% CI 1.35–5.59). Conclusions: Since almost all cases have both smoked and were highly exposed, reliable risk detection is difficult. Nevertheless, in view of a threefold increased risk, the early detection of urinary bladder carcinomas were promising.